The Association of Ursodeoxycholic Acid Use With Colorectal Cancer Risk: A Nationwide Cohort Study. Issue 11 (March 2016) - Huang, Wen-Kuan; Hsu, Hung-Chih; Liu, Jia-Rou; Yang, Tsai-Sheng; Chen, Jen-Shi; Chang, John Wen-Cheng; Lin, Yung-Chang; Yu, Kuang-Hui; Kuo, Chang-Fu; See, Lai-Chu
Abstract : Abstract: Data from preclinical studies suggest that ursodeoxycholic acid (UDCA) has a chemopreventive effect on colorectal cancer (CRC) development, but no large observational study has examined this possibility. The aim of this study was to investigate the association of UDCA use with CRC risk in a nationwide population-based cohort. This nationwide population-based cohort study used data from the Taiwan National Health Insurance Research Database for the period from 2000 through 2010. This study included data from 7119 Taiwanese adults who received ≥28 cumulative defined daily doses (cDDDs) of UDCA and 14, 238 patients who did not receive UDCA (<28 cDDDs). UDCA nonusers were matched 1:2 for age, sex, enrollment date, and presence of chronic liver disease, viral hepatitis, cholelithiasis, and alcoholic liver disease. The 2 cohorts were followed until December 31, 2010 or occurrence of CRC. Cox proportional hazards regression with robust Sandwich variance estimator, which can cooperate with matching design, was used to examine the association between UDCA use and CRC risk. During 109, 312 person-years of follow-up (median, 5 years), 121 patients had newly diagnosed CRC: 28 UDCA users (76.7 per 100, 000 person-years) and 93 nonusers (127.7 per 100, 000 person-years) (log-rank test, P = 0.0169). After multivariate adjustment for age, UDCA use was associated with a reduced risk of CRC (hazard ratio, 0.60; 95% confidence interval [CI], 0.39–0.92). The adjusted hazard ratios were 0.55 (95% CI, 0.35–0.89), 0.89 (95% CI, 0.36–2.20), and 0.63 (95% CI, 0.16–2.53) for patients with 28 to 180, 181 to 365, and >365 cDDDs, respectively, relative to nonusers. UDCA use was associated with reduced risk of CRC in a cohort mainly comprising patients with chronic liver diseases. However, further studies are needed to determine the optimal dosage of UDCA.